PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP PELAKSANAAN KEGIATAN EKSTRAKURIKULER PMR DI SMK N 1 KOTA JAMBI - Safa Panuluh, Safa Panuluh; Firman, Firman; Bradley Setiyadi , Bradley Setiyadi (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2023)
This study aims to determine the effect of Principal Leadership and Organizational Culture on PMR Extracurricular Activities at SMK N 1 Jambi City. The study used quantitative methods and the research data were obtained by distributing questionnaires to students who were members of PMR. The population in this study were PMR members at SMK N 1 Jambi City. The sample in this study amounted to 30 students with sampling techniques using total sampling techniques. The results of this study indicate that: (1) There is an influence of the principal's leadership on PMR extracurricular activities. This is evidenced by the results of the t test with a tcount value greater than the ttable value, namely 2.272> 2.052, with a percentage of 15.6%. (2) There is an influence of organizational culture on PMR extracurricular activities. This is evidenced by the results of the t test with a tcount value greater than the ttable value, namely 3.295> 2.052 with a percentage of 27.9%. (3) There is an effect of principal leadership and organizational culture on PMR extracurricular activities. This is evidenced by the results of the t test with a tcount value greater than the ttable value, namely 9,779> 3.34 with a percentage of 42%, the remaining 58% is influenced by other variables not discussed in this study. Â Keywords: Leadership, Organizational Culture, Extracurricular, PMR.